Potentials of African nutmeg (Monodora myristica) as a flavourant in cookie production - Kazeem K. Olatoye; Omololu O. Fapojuwo; Joshu A. Olorunshola; Julianah O. Ayorind (International Journal of Food Studies)
African nutmeg, a possible local substitute for a commercial food flavourant, remains largely underutilized in Nigeria. Its application potential in cookie production was investigated in this study. African nutmeg (Monodora myristica) seed flour (ANM) was produced using a standard method. The flour was substituted for vanilla flavour (VFL) in ratio of 0, 1, 2, 3, and 3.5 g and functional properties of the flour blends (water absorption capacity (WAC), oil absorption capacity (OAC), and bulk density) were determined, using standard methods. Cookies were developed and characterized chemically, physically (colour) and organoleptically using the AOAC method, a colourimeter and sensory panellists respectively. Data were analysed using ANOVA at p<0.05. Replacement of vanilla with African nutmeg had no significant effect on bulk density (0.62 g cm−3 -0.68 g cm−3 ), but significantly affected WAC (133-142 %) and OAC (147-156 %) of flour blends. Crude protein (9.44-15.49 %), crude fat (3.17-6.50 %), total ash (2-2.73 %) and crude fibre (0.12-0.23 %) contents of the cookie increased, whilst metabolizable energy (385.33-367 kcal) decreased. There were reductions in pH (6.83-6.53) and TSS (5.80-1.20). Brown index of the snack increased with addition of nutmeg. Antioxidant indicators (flavonoids, DPPH and phenol) varied among cookie samples. Antinutrients, saponin, tannin and oxalate, were within tolerable limits. All cookie samples were judged acceptable by the panellists, with SLZ being the most acceptable. An acceptable and nutritious snack was produced at 100 % replacement. M. myristica seed could serve as substitute for vanilla in the production of cookies and other related snacks.